Escenas y escenarios: Itinerarios de los estudios teatrales (EDITUM. Ediciones de la Universidad de Murcia, 2025)
Scene and scenarios: Itineraries of theatrical studies, edited by Isabel Guerrero and Alba Saura-Clarres, is born from the desire to discover different camnios that run through theatrical studies, drawing a cartography for dissimilar scenes and scenarios of the world to let us guide for the various focidque each theater researcher presents us in their act of expectation. In this way, the book proposes to explore the multiple perspectives of theatrical research gathering twelve studies that account for the breadth and wealth of the field. In them, the researchers who accompany us express their scientific work and reveal their role as spectators of the theatrical event and its components.